A case of complicated parapneumonic pleural effusion caused by paragonimus infection in a child was successfully treated by intrapleural injection of urokinase: a case report and literature review - Shi, Yangyi; Li, Yan; Hu, Yu (Frontiers in Pediatrics, 2025)
ObjectiveThe clinical data of a child with complex parapneumonic effusion (PPE) caused by pneumofluke infection were analyzed, and the diagnosis and treatment of the disease were discussed through literature review. The effectiveness and safety of urokinase in the treatment of complex PPE and empyema caused by multiple pathogens were emphasized.MethodsA 3-year-old male child with pneumofluke infection was admitted to the pediatric department of Mianyang Central Hospital. Chest CT and chest ultrasound showed a right pleural effusion with dense septum formation. The condition was relieved after treatment with praziquantel for anti-infection, thoracic catheter drainage, and urokinase injection into pleural cavity. Through systematic literature search of Pubmed, Embase, CNKI, Wanfang and VIP Chinese databases, no cases of urokinase treatment of pleural effusion caused by pneumofluke infection were found.ResultsA total of 150 ml thick yellow turbidous fluid was drained out of the pleural cavity, and the patient's symptoms and signs were significantly relieved. Reexamination of the chest CT showed that the right pleural effusion was significantly reduced and the right lung was significantly reexpanded. There were no complications such as bronchopleural fistula, pneumothorax, abnormal coagulation function, bleeding and fever during treatment.ConclusionThoracic catheter drainage combined with injection of urokinase is an effective and safe method for the treatment of complex PPE and empyema caused by pneumofluke infection in children. At the same time, the literature review showed that urokinase injection into pleural cavity was effective in the treatment of complex PPE and empyema caused by infection, trauma, tumor and other causes, and no obvious side effects occurred.